Comparison of clinical outcomes in patients with acute ischemic stroke who underwent endovascular treatment using different perfusion modalities: a real-world multicenter study - Gao, Jiali; Jing, Zhen; Huang, Shengming; Yang, Jiajie; Guan, Min; Zhang, Shijun; Li, Hao; Li, Yongxin; Lu, Kui; Yang, Ming; Huang, Li’an (Frontiers in Neurology, 2023)
BACKGROUND: Advanced perfusion modalities are increasingly popular for various diseases. However, few studies have focused on contrasting perfusion patterns.Compare the time efficiency and clinical outcomes of patients with acute ischemic stroke (AIS) who underwent endovascular treatment (EVT) before onestop arterial spin labeling (ASL) and computed tomography perfusion (CTP) protocols.This study retrospectively included 326 patients with AIS who have accepted EVT within 24 hours of onset from four comprehensive stroke centers between October 2017 and September 2022. After 1:1 matching of the propensity scores, 202 patients were separated into two groups: the ASL group (n=101) and the CTP group (n=101).Functional independence at 90 days (modified Rankin Scale [mRS] 0-2; p=0.574), onset-to puncture time (p=0.231), door-to-puncture time (p=0.136), and door-to-perfusion time (p=0.646) were not significantly different between the two groups. The proportion of EVT complications (31.7% in the ASL group vs. 14.9% in